PROPOSED POLICY DESIGN FOR NICKEL DOWNSTREAM INDUSTRY PROGRAM USING SYSTEM DYNAMICS APPROACH - Fatih Barkah, Ahmad
The growth and resilience of the nickel industry are key elements of global industrialization and technological progress. This study presents a system dynamic approach towards policy formulation and strategic planning in the nickel industry downstream sector by constructing a model to analyze and estimate the impact of different policy scenarios on nickel downstream strategies. The system dynamics model incorporates various interdependencies and feedback loop characteristics of the nickel supply chain, such as mining, smelting, refinement, supply, demand, and policy alterations. The model provides an in-depth comprehension of the dynamics affecting industry growth and the downstream sector responses to various policy initiatives by simulating a variety of possible future scenarios. The key contributors to the nickel downstream industry program were determined by conducting a variety of literature reviews. A material flow analysis depicting some of the industrial stakeholders and variables was used to create a map of the industrial situation and its material flows. Literature and investigations revealed that the key variables were ore supply and demand for the final product, product prices, industry capacity and its costs, and state revenues. Indonesia, a prominent producer of various minerals, including nickel, still lacks of welldeveloped nickel-based industry, particularly in the intermediate nickel sector. This deficiency leads to the country's reliance for exporting on several types of semi-finished nickel products required by its downstream industries. Furthermore, Indonesia primarily exports nickel concentrates and some smelting products, resulting in suboptimal value addition from its nickel resources. To address this issue and maximize the added value, research was conducted on the downstream nickel industry to estimate its potential increase. The study employed a system dynamics model to simulate the period from 2023 to 2043. The findings indicate that by completing the planned low grade nickel ores (LGNO) smelters and refineries by 2028, processing all domestic concentrates, and enhancing the capacity of the intermediate industry, Indonesia could achieve a total state revenue of 1.4 billion USD in the nickel industrial downstream sector.